Recent advances in conducting tissue engineering based on conducting polymers - Oktay, Busra; Akkad, Haya; Ahlatcioglu Ozerol, Esma (TAYLOR & FRANCIS LTD, 2026)
Conductive tissue engineering has emerged as a revolutionary approach to addressing the limitations of traditional regenerative therapies by integrating electrical and mechanical properties into biomaterials. This field focuses on mimicking the natural microenvironment of excitable tissues, such as nerves, cardiac, and skeletal muscles, to enhance cellular functions and facilitate tissue repair. Conducting polymers (CP), including polypyrrole, polyaniline, and PEDOT, have been widely utilized for their exceptional electrical conductivity, biocompatibility, and tunable properties. The incorporation of these polymers into electroactive scaffolds has demonstrated significant potential in promoting cell proliferation, differentiation, and alignment, while also enabling functional recovery through electrical stimulation. Applications in nerve regeneration have shown promise in restoring synaptic connections, while in cardiac and skeletal muscle tissues, conductive scaffolds aid in synchronized contractions and structural reinforcement. Despite these advancements, challenges such as optimizing conductivity, achieving long-term biocompatibility, and scaling production remain key areas of focus. This review thoroughly examines the use of conducting polymers for different tissue types such as neural, cardiac, and muscular tissues in light of the most recent literature. By addressing key topics such as electrical stimulation, multifunctional scaffold systems, biological responses, and emerging research trends, this study presents a holistic and up-to-date contribution to the field. Future directions aim to refine scaffold designs, enhance electrical stimulation protocols, and explore translational potential, paving the way for advanced regenerative therapies.
Keywords: Conducting polymers; conductive tissue engineering; PEDOT; polyaniline; polypyrrole; CARDIAC TISSUE; DIFFERENTIATION; COMPOSITES; SCAFFOLDS; SUBSTRATE; MEMBRANE; HYDROGEL; Engineering; Materials Science; Polymer Science